2020
DOI: 10.1111/theo.12275
|View full text |Cite
|
Sign up to set email alerts
|

Truth or Accuracy?

Abstract: An important conceptual shift can be discerned within contemporary philosophy of perception. Whereas proponents of the idea that perceptual experience is contentful used to relate perceptual content to truth conditions, authors nowadays prefer to think of perception as evaluable for accuracy. This transition from truth to accuracy becomes particularly clear in the influential work of Susanna Siegel. Importantly, Siegel actually provides an extensive argument for this shift. Yet this article argues that this tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Notice, first, that D6 deliberately does not specify a priori whether mistaken tokening amounts to information being false or simply inaccurate. Several philosophers have recently shifted to attributing, at least to perceptual states, accuracy rather than truth conditions [70][71][72][73]. Accuracy and truth are related, but have distinct properties, for the latter is binary (at least under classical logic), whereas the former admits of degrees [70] (p. 458).…”
Section: (D6) Mistaken Tokeningmentioning
confidence: 99%
“…Notice, first, that D6 deliberately does not specify a priori whether mistaken tokening amounts to information being false or simply inaccurate. Several philosophers have recently shifted to attributing, at least to perceptual states, accuracy rather than truth conditions [70][71][72][73]. Accuracy and truth are related, but have distinct properties, for the latter is binary (at least under classical logic), whereas the former admits of degrees [70] (p. 458).…”
Section: (D6) Mistaken Tokeningmentioning
confidence: 99%
“…10 Pojęcie warunków adekwatności utrwaliło się dzięki pracy Susanny Siegel (2010), jednakże podany tam argument na rzecz odróżnienia warunków prawdziwości od warunków adekwatności jest wysoce problematyczny (Zahnhoun 2020). Dyskusję komplikuje fakt, że niektórzy autorzy uważają różnicę między propozycjonalną i niepropozycjonalną treścią reprezentacyjną (oraz odpowiadającą jej różnicę między warunkami prawdziwości oraz warunkami adekwatności) za w gruncie rzeczy mało istotną lub dającą się zignorować (np.…”
Section: Realizm Naiwnyunclassified
“…These values of soil losses are close to the results obtained by various researchers who have worked in northern Morocco. These studies have found erosion rates as high for instance 65 t/ha/year was estimated at the level of the Nakhla watershed [5], and 55.35 t/ha/year at the level of Oued Boussouab in the eastern Prérif [4], 46.1 t/ha/year in the northeast at Oued Tlata [6] and 49.59 t/ha/year for the basin of Oued Larbaa and 43.68 t/ha/year on average for the catchment area of Oued Beni Boufrah, Central Rif [7]. On the other hand, the study conducted in the Middle Atlas as that of Hili [2] whose objective was also to estimate the erosion of a watershed Oued Amlil.…”
Section: Erosion Coefficient (Z)mentioning
confidence: 99%